Development of a biointegrated mandibular reconstruction device consisting of bone compatible titanium fiber mesh scaffold. (January 2016) - Hirota, Makoto; Shima, Takaki; Sato, Itaru; Ozawa, Tomomichi; Iwai, Toshinori; Ametani, Akihiro; Sato, Mitsunobu; Noishiki, Yasuharu; Ogawa, Takahiro; Hayakawa, Tohru; Tohnai, Iwai
Abstract: Coating biomaterials with a thin hydroxyapatite (HA) was proven effective in enhancing bone compatibility. Segmental bone defects are considered as the most difficult defect to repair in bone regeneration therapy. We developed submicron-thin HA-coated titanium fiber mesh scaffolds to reconstruct immediately loaded segmental mandibular defects and evaluated their bone compatibility in vitro and in vivo . Human osteoblasts attachment, proliferation, and osteocalcin expression in non- and HA-coated scaffolds were evaluated. A 10-mm long segmental bone defect in a rabbit mandibular bone was reconstructed with non- or HA-coated scaffolds, which were removed at 9 and 21 weeks, to evaluate the mechanical strength of the bone-scaffold connection and the bone formation around the scaffold. Expression of osteocalcin was greater in HA-coated scaffolds. In vivo bone formation in HA-coated scaffolds was greater than that in non-coated scaffolds at 21 weeks. Newly formed bone in HA-coated scaffolds mostly restored bone continuity. Scanning electron microscopy identified strong integration of the bone and HA-coated scaffolds. The mechanical strength of the bone-scaffold connection was 3-fold greater in HA-coated scaffolds than that in non-coated scaffolds. These results suggest that a thin HA-coated titanium fiber mesh scaffold is a bone-compatible mandibular reconstruction device in immediately loaded segmental defects.